The generation of intense heat fluxes by electron bombardment to evaluate the use of swirl flow in the cooling of accelerator targets - Genis, Gerrit Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Phil) -- University of Stellenbosch, 1985.